Puesta en valor de una escuela patrimonial en zona de alto riesgo sísmico: un caso de estudio - Maldonado, N. G.; MartínP.; Maldonado, I.; Calderón, F. (Revista ALCONPAT, 2014)
The Mitre School is a monumental building enabled in 1906 using fired ceramic masonry without tie-reinforcement. During its service life it has suffered damages from impulsive earthquakes in Mendoza, Argentina, as well as from changes in the materials and lack of maintenance. The methodology of study included the following stages: a detailed inspection, emergency decisions, analysis of conservation state of the building, as well as the diagnosis and rehabilitation alternatives. With the data from the field and laboratory tests, the building was modeled by using finite elements. The advantages of the use of concrete in the rehabilitation include the lowest cost and the best structural performance according to rehabilitation standards in force; nonetheless, from the standpoint of heritage, the combination of steel structures, that do not interfere with the original factory, and the rehabilitation of reinforced concrete foundations are preferred. Keywords: heritage, safety, seismic resistant, enhancement.